Upgrade and benchmarking of a 4D treatment planning system for scanned ion beam therapy - Richter, Daniel; Schwarzkopf, A.; Trautmann, J.; Krämer, M.; Durante, M.; Jäkel, Oliver; Bert, C. (Medical physics, 2013)
Purpose: Upgrade and benchmarking of a research 4D treatment planning system (4DTPS) suitable for realistic patient treatment planning and treatment simulations taking into account specific requirements for scanned ion beam therapy, i.e., modeling of dose heterogeneities due to interplay effects and range changes caused by patient motion and dynamic beam delivery. Methods: The 4DTPS integrates data interfaces to 4D computed tomography (4DCT), deformable image registration and clinically used motion monitoring devices. The authors implemented a novel data model for 4D image segmentation using Boolean mask volume datasets and developed an algorithm propagating a manually contoured reference contour dataset to all 4DCT phases. They further included detailed treatment simulation and dose reconstruction functionality, based on the irregular patient motion and the temporal structure of the beam delivery. The treatment simulation functionality was validated against experimental data from irradiation of moving radiographic films in air, 3D moving ionization chambers in a water phantom, and moving cells in a biological phantom with a scanned carbon ion beam. The performance of the program was compared to results obtained with predecessor programs. Results: The measured optical density distributions of the radiographic films were reproduced by the simulations to (−2 ± 12)%. Compared to earlier versions of the 4DTPS, the mean agreement improved by 2%, standard deviations were reduced by 7%. The simulated dose to the moving ionization chambers in water showed an agreement with the measured dose of (−1 ± 4)% for the typical beam configuration. The mean deviation of the simulated from the measured biologically effective dose determined via cell survival was (617 ± 538) mGy relative biological effectiveness corresponding to (10 ± 9)%. Conclusions: The authors developed a research 4DTPS suitable for realistic treatment planning on patient data and capable of simulating dose delivery to a moving patient geometry for scanned ion beams. The accuracy and reliability of treatment simulations improved considerably with respect to earlier versions of the 4DTPS.
Gesehen am 11.01.2022